Treatment of chronic apical periodontitis on the basis of the modern concept of endodontics (clinical case) (LLC "Endo Press", 2020)
Repeated endodontic treatment is often a contentious issue in the process of making a final decision in the preparation of a comprehensive plan for the treatment of a patient at the dental reception and causes great interest among dentists. For the successful outcome of root canal treatment is important not only knowledge and manual skills of the doctor, but also equipping the workplace with modern materials and technologies. This article describes a clinical case of repeated endodontic treatment of tooth 2.1 and carried out a detailed analysis of his. At the final stage represented the final result after 1 week of treatment. This article will help doctors - dentists acquire additional knowledge needed to effectively address not only repeat, but the primary endodontic treatment.